(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
Boswellia papyrifera is an important resource in the dryland ofthe Blue Nile State. However, its population is declining due to manybiological and environmental factors. Moreover, there was hardly anyregeneration of the species in its natural habitat. The objectives of thisstudy were to count the new regeneration of seedlings, before and afterrainfall, to assess the viability of B. papyrifera seeds in the soil seed bank,to detect the effect of soil types on seedlings’ growth and to determine theoptimum diameter and time of cutting. Natural regeneration surveys werecarried out in the field by counting the young seedlings at differentelevations before and after the rains. Soil samples from plots 2x2 metreswere randomly collected. B. papyrifera seeds were sown in two types ofsoil mixes namely, 1 sand: 2 silt by volume; and in soil collected from thesite where B. papyrifera trees are growing. Branch cuttings of one meterlength and 4-5cm and 6-7cm in diameter, each, were taken at threedifferent dates, namely first of April, mid of April and first of May andplanted in the nursery. The results showed that B. papyrifera producedplenty of seeds that were stored in the soil seed bank. However, seedlingswere almost absent after the dry season. A significant (P<0.05) differencewas found between the mean number of seedlings growing at the foot ofthe mountain and the slope as compared to those growing on top of themountain. A significant (P≤0.05) difference was found between the meanheight of seedlings raised in the two types of soils. There was nosignificant difference between the number of survived branch cuttings dueto planting date and/or branch diameter, but large diameter cuttingsshowed better results. These results suggest that additional managementinterventions, such as artificial regeneration, to support early seedlings